Suara Kosong pada Pilkada Serentak di Indonesia: Perspektif Hukum Tata Negara Islam - Mangar, Irma; Tahe , Nur-amimi; Ridho , Muhammad Rosyid; Asri Elies, Asri Elies; Sudrajat, Shinta Azzahra; Luluardi, Yunas (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
The increasing number of single candidates and blank votes in the simultaneous regional elections is a fact in the democratic process in Indonesia. This paper discusses blank votes in simultaneous regional elections, which are a dilemma in enforcing the principles of democracy. Furthermore, it discusses blank votes from the perspective of Islamic constitutional law. The research method uses normative juridical with a statutory, conceptual and case approach. The results show that the fact of single candidates in the simultaneous regional elections which are legitimized by laws and regulations opens up the opportunity for blank votes to emerge which are